Enhancing Employee Agility Through Information Technology Competency: An Empirical Study of China. (April 2021) - Lai, Han; Pitafi, Abdul Hameed; Hasany, Noman; Islam, Tahir
This study investigated how employees' information technology (IT) competency is associated with employee agility via perceived task structure. Most scholar's emphasis is on the impact of IT competency on individual work performance; however, it seems as if no attention has been given to explore the relationship between IT competency on employee's agility through perceived task structure. This research offers and tests a new comprehensive model that links the individual's IT competency with perceived task structure and employee agility. Data were gathered from 167 representatives who used various IT applications for daily work routines in the organization. Findings showed that IT competency is positively related to task interdependence and autonomy. Task autonomy also has significant effect on employee agility; however, task interdependence has shown insignificant effect on employee agility. Furthermore, work expertise positively moderates the relationship between IT competency and perceived task structure. Theoretical and managerial implications of study are also discussed in the last section.